Betrayal Aversion and the Effectiveness of Incentive Contracts - Holger Rau; Stephan Müller (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
In this paper we study the impact of betrayal aversion on agents' effort provision, when principals have discretion regarding agents' remuneration. We show theoretically that agents who work under a nonbinding bonus contract face a trade off in their effort choice between the likelihood and the level of betrayal. Thus, depending on which effect predominates, betrayal aversion may either undermine or underpin the effectiveness of bonus contracts to induce effort. The data of our experiment reveal a strong detrimental effect of betrayal aversion. If the principal promises to pay a bonus for sufficiently high effort, the message is ineffective when agents are characterized by a high degree of betrayal aversion. In strong contrast, employees with a low degree of betrayal aversion increase their performance by more than 50%, if they received this message. The findings in this article identify an additional hidden cost of economic incentives.
Keywords: C91; D03; D81; 330; Betrayal Aversion; Principal Agent Problem; Experiment